2020
DOI: 10.1186/s12933-020-01176-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on atrial and ventricular arrhythmias: evidence from cell to patient

Abstract: Metformin has been shown to have various cardiovascular benefits beyond its antihyperglycemic effects, including a reduction in stroke, heart failure, myocardial infarction, cardiovascular death, and all-cause mortality. However, the roles of metformin in cardiac arrhythmias are still unclear. It has been shown that metformin was associated with decreased incidence of atrial fibrillation in diabetic patients with and without myocardial infarction. This could be due to the effects of metformin on preventing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 95 publications
(135 reference statements)
2
26
0
1
Order By: Relevance
“…36,83 Metformin, a widely used anti-diabetic drug is considered to have potential beneficial effects beyond its antihyperglycemic action, and has been shown to ameliorate mitochondrial dysfunction, calcium dysregulation and repolarization abnormalities in animal models, in addition to decreasing plasma BCAA levels and activating AMPK. 84,85 However, whether these approaches also reduce arrhythmia risk remains to be investigated. Sodiumglucose cotransporter (SGLT2) inhibitors are now recommended as antidiabetic therapy, and have recently shown promising anti-arrhythmic effects in diabetic patients.…”
Section: Weight Loss Bariatric Surgery and Dietary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,83 Metformin, a widely used anti-diabetic drug is considered to have potential beneficial effects beyond its antihyperglycemic action, and has been shown to ameliorate mitochondrial dysfunction, calcium dysregulation and repolarization abnormalities in animal models, in addition to decreasing plasma BCAA levels and activating AMPK. 84,85 However, whether these approaches also reduce arrhythmia risk remains to be investigated. Sodiumglucose cotransporter (SGLT2) inhibitors are now recommended as antidiabetic therapy, and have recently shown promising anti-arrhythmic effects in diabetic patients.…”
Section: Weight Loss Bariatric Surgery and Dietary Interventionsmentioning
confidence: 99%
“…88 Drugs that modulate AMPK activity, such as for instance metformin and resveratrol, may also prove to have anti-arrhythmic effects. 71,85 As reviewed by Ren et al, 36 additional potential strategies include those targeting autophagy, adiponectin, inflammation (NF-kB, cytokines, TGF-beta), PPARɣ, as well as epigenetically based pharmacotherapies inhibiting DNA methyltransferases and histone deacetylases. However, their anti-arrhythmic effects remain as yet unexplored.…”
Section: Weight Loss Bariatric Surgery and Dietary Interventionsmentioning
confidence: 99%
“…(46) A direct antiarrhythmic effect of MET has been postulated as well. (47) Although QoL was independent of DM status in our study, we have observed a better QoL in MET-treated DM patients and MET was signi cantly associated with QoL also in multivariable linear regression suggesting its independent effect on QoL. To our best knowledge, this is the rst study that analyzed the QoL with respect to MET treatment using a validated tool.…”
Section: Discussionmentioning
confidence: 42%
“…Metformin has many benefits in the case of cardiovascular protection such as left ventricular mass, myocardial infarction, cardiovascular death, reduction in blood pressure, heart failure, stroke, and all-cause mortality [39]. It also increases ketone body metabolism, promotes fatty acid oxidation, reduces lipid accumulation, induces the expression of glucose transporter in cardiomyocytes, all of which happened due to the activation of 5′-adenosine monophosphate-activated protein kinase, and it also facilitated efficient energy use with reduction of metabolic stress [40,41].…”
Section: Metformin Role In Af Patientsmentioning
confidence: 99%
“…To decrease the incidence of AF in diabetic patients with and without myocardial infarction, metformin was associated to prevent the structural and electrical remodeling of the left atrium through improving calcium homeostasis, attenuating inflammation, activating 5′ adenosine monophosphate-activated protein kinase, increasing connexin-43 gap junction expression, attenuating intracellular reactive oxygen species, restoring small conductance calcium-activated potassium channels current [39]. Metformin is recommended for the treatment of type 2 diabetes mellitus and exerts an insulin-sensitizing effect [42] and might have anticancer, anti-inflammatory and antimicrobial and antiaging effects [43][44][45][46].…”
Section: Metformin Role In Af Patientsmentioning
confidence: 99%